Mangiferin and mangiferin-containing leaf extract from Mangifera foetida L for therapeutic attenuation of experimentally induced iron overload in a rat model - Ari Estuningtyas; Tri Wahyuni; Pustika Amalia Wahidiyat; Ernie H Poerwaningsih; Hans-Joachim Freisleben (Shahrekord University of Medical Sciences, 2019)
Introduction: Thalassemia is a hereditary anemia usually treated with regular blood transfusions, which can result in elevated levels of total iron in the body. As soon as the capacity of iron-regulating proteins (e.g., ferritin, transferrin) are used up, free plasma iron increases generating reactive oxygen species (ROS), leading to oxidative stress. Hence, blood transfusions should be accompanied by iron-chelating therapy, e.g., deferiprone (DFP). The purpose of this study was to evaluate the effect of mangiferin (M) and an aqueous leaf extract of Mangifera foetida L (EMF) as alternative iron-chelating antioxidants in an animal model. Methods: Thirty male Sprague Dawley rats were randomly divided into 5 equal groups: normal control, iron overload (IO), IO+DFP, IO+M, and IO+EMF. Iron overload was induced by intraperitoneal iron dextran injection with a total dose of 90 mg/mouse (15 mg Fe/mouse every 3-4 days for 3 weeks) followed by oral administration of DFP 462.5 mg/kg, mangiferin 75 mg/kg, or EMF 2.930 g/kg for 7 days. Results: Body weight (BW) increased in all groups during the 4 weeks of experiment, except for the IO group. As expected, DFP decreased significantly the total plasma iron and increased iron excretion via urine in iron-overloaded rats (positive control), mangiferin and EMF had similar - although slightly smaller - effects than DFP. The antioxidant activity of M and EMF were stronger compared to DFP as determined by plasma superoxide dismutase (SOD) activity. Conclusion: Mangiferin and EMF have iron-chelating and antioxidant effects and might be used for the treatment of iron overload in the body.